Initial Evidence for the Reliability and Validity of the Student Risk Screening Scale With Elementary Age English Learners. (September 2014) - Lane, Kathleen Lynne; Richards-Tutor, Catherine; Oakes, Wendy Peia; Connor, Kristin
We report findings of a validation study exploring the Student Risk Screening Scale (SRSS; Drummond, 1994) for use with English learners (ELs) attending a large suburban elementary school. First, we explored the reliability of the SRSS by examining internal consistency, with results indicating adequate internal consistency (.83). Second, we examined and established a convergent validity of the SRSS scores with the social skills improvement system–performance screening guide (SSiS-PSG; Gresham & Elliott, 2007) and the systematic screening for behavior disorders (SSBD; Walker & Severson, 1992). Results indicated that SRSS scores were negatively correlated with SSiS-PSG scores, thereby suggesting that an increased behavioral risk is associated with decreases in teacher-reported reading performance, math performance, motivation to learn, and prosocial behaviors. In addition, the results yielded additional evidence of convergent validity with SSBD and SRSS scores. SRSS scores improved the chance estimates of predicting the internalizing behaviors of ELs (area under the curve [AUC] = .72) and externalizing behaviors of ELs (AUC = .98) as measured by the SSBD. Third, we examined the relation between SRSS scores and academic performance as measured by dynamic indicators of basic early literacy skills Next (Good & Kaminski, 2011), which suggested an inverse relation ( r = −.41). Fourth, we examined the teachers' perceptions of the screening tool.